(untitled) (Security Dialogues, 2024)
International law safeguards our universal commons and international peace and security while protecting those the most vulnerable to human rights abuses, such as participants in existing migration towards the European Union. This article aims to shed light on the link between two international law fields: gender equality and the protection of victims of human trafficking among migrants who diverted their journey through the Western Balkan Route embracing Bosnia and Herzegovina since 2018. The research’s relevance is found in statistics from 2018 to 2022 and recent studies on the inadequate protection of migrants from human traffickers and smugglers along the Western Balkan Route. Thus, the article argues that the gender inequality in the law enforcement agencies in Bosnia and Herzegovina hinders proper identification and protection of VHT in joint migrations of men, women and children, enabling their further trafficking towards the European Union. The methodological framework includes the desk analysis of the gender mainstreaming legal framework and goes over international and national regulations on combating human trafficking. Qualitative research on the main impediments to the identification of the victims of human trafficking includes responses from NGO practitioners mandated to protect migrants in the temporary reception centres in Bosnia and Herzegovina, highlighting the presence of the VHT among migrants. Research results present the flagship components of migrants’ negligence in reporting human trafficking; one of the principal reasons is their non-confidence in law enforcement agencies, which are seriously discriminated against women regarding participation and management position holding. The article demonstrates the intersectionality of international law focus areas in the gender participation-gender protection pendulum and urges for increased participation of women in the security sector of Bosnia and Herzegovina and enhanced protection of the victims of human trafficking through international law implementation.